Brazilian guideline for pediatric cycloplegia and mydriasis - Curi,Ian (2022)
ABSTRACT Cycloplegia is crucial for reliable pediatric ophthalmology examinations. This document provides a recommendation for pediatric cycloplegia and mydriasis for Brazilian ophthalmologists. This article was developed based on literature reviews; the clinical experience of Brazilian specialists, as obtained through questionnaires; and the consensus of the Expert Committee of the Brazilian Pediatric Ophthalmology Society. According to the best evidence and formulations available in Brazil, this committee recommends the use of one drop of 1% cyclopentolate plus one drop of 1% tropicamide in children older than 6 months and two drops of 1% tropicamide 0-5 minutes apart for those younger than 6 months. Mydriasis may be increased by a single drop of 2.5% phenylephrine. For retinopathy of prematurity screening, the recommendation is 0.5% or 1% tropicamide, administered two or three times, 5 minutes apart, and 2.5% phenylephrine, used preferably once. In all scenarios, we recommend the use of a prior drop of 0.5% proxymetacaine.